Exploring Students’ Public Speaking Anxiety: Introvert vs Extrovert - Benni Ichsanda Rahman Hz (English Department - University of Sultan Ageng Tirtayasa, 2022)
This study aims to investigate whether students with introverted and extroverted personalities have significantly different levels of anxiety or not. This study involved 59 students of the English Education Study Program at one of the state universities in North Sumatra. Samples were taken randomly from five classes of sixth semester students who took the Public Speaking course. Semi-structured technique was used in data collection. The data was processed by using two methods; statistical calculations for quantitative data related to the results of filling out questionnaires regarding their level of anxiety when doing public speaking which consists of 17 questions, as well as substantive analysis for qualitative data related to the results of comparison of responses from respondents. The results shows that that 31.03% of introvert students having high anxiety, followed by 68.97% students possessing moderate level of public speaking anxiety. In contrary, 13.33% of extrovert students having high anxiety, followed by 86.67% of them having moderate level of anxiety. The biggest anxiety of respondents is in context “my heart pounds when I give a speech”, where introvert students averagely in 4.03 and extrovert students in 3.03. There are numerous suggestion that students and educators can use to overcome the issues.